Pengaruh Persepsi Kegunaan, Persepsi Kemudahan dan Kepercayaan Terhadap Minat Penggunaan Dompet Elektronik (OVO) Sebagai Media Transaksi Keuangan - Putri, Putu Desya Srinadi; Latrini, Made Yenni (Jurnal Ilmiah Wahana Pendidikan, 2024)
OVO electronic wallet is an electronic wallet application that has service features to make it easier for users to make financial transactions anywhere and at any time. OVO is one of the leading electronic wallet applications and is very often used by students at the Faculty of Economics and Business, Udayana University because not only has service features as a financial transaction, but this application have insurance payment, loan and investment service features. This study aims to determine the influence of perceived usefulness, perceived ease of use and trust intention to use electronic wallets (OVO) as a media for financial transactions. This research data was obtained using a questionnaire distributed to 104 respondents who were active students at the Faculty of Economics and Business, Udayana University, Class 2020-2022. The sample used in this research was the purposive sampling method. The data analysis method used is multiple linear regression analysis. This research supports the TAM theory (Technology Acceptance Model) and Behavioral Intention. The research results show that perceived usefulness, perceived convenience and trust have a positive effect on interest in using electronic wallets (OVO) as a financial transaction.